HRD on the Margins: Exploring Resistance to HRD in Adult Education - Alisa Belzer; Laura L. Bierma; Maria Cseh; Andrea Ellinger; Wendy Ruona; Karen Watkins (Adult Education Research Conference, 2001)
This paper examines the debates and critiques surrounding HRD and confronts myths about HRD philosophy and practice. We argue that the HRD field is "marginalized" in adult education and reflect on both the problems this situation creates and the possibilities of ever bridging these two fields.